Penggunaan Media Papan Flanel Dalam Meningkatkan Hasil Belajar Siswa Pada Pembelajaran Bahasa Arab - Prihandini, Ananda; Fajriyatul Fahyuni, Eni (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
.  In the current era, Arabic is considered a difficult and boring lesson when in class, with the media of learning activities, learning Arabic in class is easier so that students will be more happy to be active and creative with the Arabic flannel board learning media which will have an impact on the value of student learning outcomes. the aim is to help make learning Arabic easier to understand the material both in terms of vocabulary, composing Arabic sentences. The type of research used is quantitative research using a pretest-posttest quasi-experimental design. The data source taken was pretest-posttest. using a population, namely all class VII students of SMP Muhammadiyah Tulangan. With the sample class 7A is the experimental class and class 7B is the control class. by using This research uses three data analysis techniques, namely normality test, homogeneity test and hypothesis test. in the form of SPSS software. The normality test uses the Kolmogrov Smirnov test to determine whether the data is normal or not. To determine whether the control class and experimental class have similar variants or not, a homogeneity test is carried out using analyze-compare mean-oneway ANOVA. and to test the hypothesis using the paired sample T-test media technique. In this research, the results of the experimental class before the application of the media showed that the average student score was 67.73 with Std. error 2.016 while after applying the media the average value was 87.23 with Std. error 2,198, shows that the use of Arabic flannel board media can improve student learning outcomes at Muhammadiyah Middle School in Sidoarjo.